Economic-financial analysis and its influence on decision making in a company providing liquid fuel service - Poma, Edilberto (2019)
The objective of the research was to evaluate the economic and financial management of the service of the National University of Puno Altiplano in the period 2015 to 2017. The service center is dedicated to the sale of liquid fuels (oil and gasoline). To achieve the objective of the investigation, the horizontal and vertical analysis was carried out, to which the evaluation was added through the indicators or financial ratios to the company's financial statements. With the analysis of the latter, the influence on decision making at the managerial level was determined. The results of the economic and financial analysis indicate that there is a significant influence according to the indicators evaluated. Faced with the results, alternatives were proposed that contribute to the solution and strengthening of the economic indicators of the company.